PEMANFAATAN LIMBAH KULIT PISANG KEPOK SEBAGAI BAHAN DASAR DALAMPEMBUATAN PUPUK CAIR (KAJIAN PENAMBAHAN EM4 DENGAN METODE AN AEROB) - Nopriyanti, Marisa; Umi Kalsum, Syarifah (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2021)
Liquid fertilizer is a fertilizer whose basic ingredients come from animals or plants that have undergone fermentation and the form of the product is in the formof a liquid. Kepok banana peel is one of the basic ingredients used for the manufacture of liquid fertilizer because it contains macro elements N, P, and K. this study aimed to determine the nutrients contained in the liquid fertilizer from barangan banana peels. This research was conducted by mixing brown sugar, water, and the effectiveness of microorganisms (EM4) with the fixed variables used were banana peels. The method used in this study was to mix 80 grams of brown sugar, 1 liter of water, and the effectiveness of microorganisms (EM4) with a variation of the composition of 200 ml, 300 ml and 400 ml with the fixed variable used was banana peels. The parameters observed were pH, yield, and total N. The results showed that the liquid fertilizer produced had a pH of 4 liquid fertilizer, the yields obtained from the 3 treatments were 2.4%, 2.5%, and 2.6%. While the total N content from the analysis process was 1.26%, 2.38, and 4.48.